Autoregulation and non-homeostatic behaviour of renal blood flow in conscious dogs. - Persson, Pontus B.; Ehmke, Heimo; Kirchheim, Hartmut; Janssen, B.; Baumann, J. E.; Just, Armin; Nafz, Benno (The journal of physiology, 1993)
1. Spontaneously occurring haemodynamic variations within 4 h affecting renal blood flow (RBF) were compared with externally induced short changes of renal artery pressure (RAP) in conscious resting dogs. 2. In all animals in which RAP was servo-controlled (n = 6), perfect autoregulation of RBF was observed. 3. In all 4 h recordings of spontaneous renal blood flow (n = 9), certain combinations of blood pressure and blood flow occurred remarkably frequently as indicated by three-dimensional frequency distributions. 4. Cluster analysis demonstrated significant differences between these areas of accumulation (P < 0.001). The average number of 'set points' per 4 h session was 3.1 +/- 0.3. 5. The shift from one set point to another is probably mediated by multiple control systems impinging on renal haemodynamics as suggested by 1/f fluctuations. 6. In seven dogs, an additional renal venous catheter allowed measurements of the arterial-venous (A-V) oxygen partial pressure (PO2) difference as an indicator of the renal metabolic demand. An inverse relationship between A-V PO2 difference and RBF (Y = X(-0.034) + 40.9, r = -0.9, P < 0.001) was found, indicating that the metabolic demands vary little (if at all) between the different set points. 7. The presented data suggest a modified view of renal homeostasis. There exist distinct combinations between RBF and RAP, which are very stable. Autoregulation merely buffers the fluctuations around these set points.
Gesehen am 04.12.2024